2013
DOI: 10.1152/ajpendo.00608.2012
|View full text |Cite
|
Sign up to set email alerts
|

G9a is transactivated by C/EBPβ to facilitate mitotic clonal expansion during 3T3-L1 preadipocyte differentiation

Abstract: In 3T3-L1 preadipocyte differentiation, the CCAAT/enhancer-binding protein-β (C/EBPβ) is an important early transcription factor that activates cell cycle genes during mitotic clonal expansion (MCE), sequentially activating peroxisome proliferator-activated receptor-γ (PPARγ) and C/EBPα during terminal differentiation. Although C/EBPβ acquires its DNA binding activity via dual phosphorylation at about 12-16 h postinduction, the expression of PPARγ and C/EBPα is not induced until 36-72 h. The delayed expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“…G9a plays important roles in various biological processes and has been shown to be a repressor of adipogenesis (27). In 3T3-L1 cells, a transient induction of G9a by C/EBP␤ was detected during MCE (32). Then, G9a inhibited PPAR␥ and C/EBP␣ expression through H3K9 dimethylation of their promoters.…”
Section: Role and Mechanism Of C/ebp␤ In Mitotic Clonal Expansionmentioning
confidence: 99%
“…G9a plays important roles in various biological processes and has been shown to be a repressor of adipogenesis (27). In 3T3-L1 cells, a transient induction of G9a by C/EBP␤ was detected during MCE (32). Then, G9a inhibited PPAR␥ and C/EBP␣ expression through H3K9 dimethylation of their promoters.…”
Section: Role and Mechanism Of C/ebp␤ In Mitotic Clonal Expansionmentioning
confidence: 99%
“…Although some C/EBPβ-regulated genes have been found, there are still a lot unknown. Our laboratory used ChIP-onchip experiments to identify a series of C/EBPβ target genes at the early stage of 3T3-L1 preadipocyte differentiation (27,(31)(32)(33)(34), among which is KLF10. In the current study, we demonstrated that the expression profile of KLF10 positively correlated with that of C/EBPβ during 3T3-L1 preadipocyte differentiation (Fig.1).…”
Section: Resultsmentioning
confidence: 99%
“…77 Furthermore, CEBPb activates G9a expression during mitotic clonal expansion reiterating a role for G9a in proliferation of preadipocytes. 78 In contrast to G9a, knockdown of SETDB1 decreased myogenic differentiation through downregulation of MyoD and myogenin expression indicating that SETDB1 is required for their expression and differentiation. However, surprisingly, overexpression of SETDB1 does not promote differentiation.…”
Section: Function In Cellular Differentiation and Senescencementioning
confidence: 94%
“…Similar to SUV39H1, G9a inhibits adipogenic differentiation. [76][77][78] This inhibition is mediated via repression of PPARg expression as well as activation of Wnt10a expression, a negative regulator of adipogenesis. Deletion of G9a or inhibition of its activity with BIX01294, reduced H3K9me2 on PPARg promoter but, interestingly, increased H3K9ac at the Wnt10a promoter.…”
Section: Function In Cellular Differentiation and Senescencementioning
confidence: 99%